2008
DOI: 10.3998/ark.5550190.0009.c05
|View full text |Cite
|
Sign up to set email alerts
|

Drug design of new antitubercular agents: 1,3-dipolar cycloaddition reaction of arylnitriloxides and 3-para-methoxy-benzylidene-isochroman-4-ones

Abstract: Five new 3',4'-substituted-spiro[isochromene-3,5'-isoxazolin]-4(1H)-ones 7-11 have been prepared in the reaction of p-R-benzadoxime 2-6 with 3-para-methoxy-benzylidene-isochroman-4-one 1. The reaction occurs by a 1,3-dipolar cycloaddition mechanism which leads to the regiospecific formation of various spiro-isoxazolines 7-11. It is concluded that rigid (O 1'group may be responsible for the biological activity observed in antitubercular test with these hyper inter-organised spiro-isoxazoline derivatives. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The 1,3-dipolar cycloaddition reaction of alkynes/alkenes with nitrile oxides, respectively, constitutes a versatile tool to access isoxazole and isoxazoline heterocycles [23][24][25] . In this context, and in continuation of our ongoing research devoted to synthesis heterocyclic compounds with promising biological and pharmacological activities via 1,3dipolar cycloaddition across dipolarophiles with exocyclic double bond with several 1,3-dipoles 16,20 . We describe a reaction between arylnitrile oxides precursors (arylaldoximes) and arylidenes-indanone derivatives in one pot, to give the desired spiroisoxazolines 3 (Scheme 1).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The 1,3-dipolar cycloaddition reaction of alkynes/alkenes with nitrile oxides, respectively, constitutes a versatile tool to access isoxazole and isoxazoline heterocycles [23][24][25] . In this context, and in continuation of our ongoing research devoted to synthesis heterocyclic compounds with promising biological and pharmacological activities via 1,3dipolar cycloaddition across dipolarophiles with exocyclic double bond with several 1,3-dipoles 16,20 . We describe a reaction between arylnitrile oxides precursors (arylaldoximes) and arylidenes-indanone derivatives in one pot, to give the desired spiroisoxazolines 3 (Scheme 1).…”
Section: Resultsmentioning
confidence: 98%
“…In addition, the spiroisoxazoline scaffold forms an integral part of many beneficial biologically active compounds. Indeed, spiroisoxazolines exhibit an extensive array of biological and pharmacological activities such as antiviral 13 , anticancer 14,17,18 , antimalarial 15 , antituberculosis 16 , antibacterial 17,19 and antiparasitic 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For general background to 1,3-dipolar cycloaddition reactions, see: Al Houari et al (2008. For the structures of related compounds, see: Akhazzane et al (2010Akhazzane et al ( , 2011; Mahfoud et al (2015).…”
Section: Related Literaturementioning
confidence: 99%
“…In the context of our research concerning the approach of dipole-dipolarophile in 1,3-dipolar cycloaddition, we have already studied the case where the dipole is an arylnitriloxide and the dipolarophiles are 2-arylidenes of tetralone (systematic name: 3,4-dihydronaphthalen-1-one) substituted by an anisopropyl group in position 4 (Al Houari et al, 2008;Al Houari et al, 2010). We have shown that the ring closure reaction is highly regiselective and also highly diastereoselective.…”
Section: S1 Commentmentioning
confidence: 99%